Glutathione and nitrite levels in induced sputum at COPD patients and healthy smokers - Turgut, Teyfik; Ilhan, Nevin; Deveci, Figen; Akpolat, Nusret; Erden, Ersin Sukru; Muz, M. Hamdi (Pioneer Bioscience Publ Co, 2014)
Objectives: The role of oxidative stress at the pathogenesis of chronic obstructive pulmonary disease (COPD) is known. The aim of this study is to investigate the oxidative stress with sputum induction that is a simple method in COPD patients and healthy smokers. Methods: Sputum induction was performed in 21 COPD patients (10 stable, 11 acute exacerbations), nine healthy smokers, and ten healthy non-smokers. Glutathione, NO2- levels, and cell counts at sputum, and plasma NO2- contents were evaluated in all subjects. Results: Mean sputum glutathione and NO2- levels were significantly higher in acute exacerbations with COPD patients than healthy smokers (P=0.007 and P<0.001 respectively), and non-smokers (P<0.001 and P<0.001 respectively). On the other hand, sputum glutathione and NO2- levels did not show significant differences between stable and acute exacerbations with COPD patients. Although, sputum glutathione levels were higher in stable COPD patients than healthy smokers', no statistically significant difference was established. In addition, sputum glutathione levels were significantly higher in healthy smokers than nonsmokers (P<0.001). Conclusions: As a result, we can say that oxidative stress increases not only in COPD patients but also in healthy smokers. In addition, sputum induction that is a simple method can be used to demonstrate to show oxidative stress.
Keywords: Glutathione; nitrite; induced sputum; chronic obstructive pulmonary disease (COPD)